Uma plataforma CCA para aplicações científicas usando conectores - Araújo, Gisele Azevedo de (2010)
This work presents Forró, a component platform for scientific applications CCA model compliant using endogenous and exogenous connectors. The main contributions of this study were: concepts proposal of link and Connecting Space for distributed components, and proposal of use endogenous connectors, exogenous connectors and ducts in CCA model, which had not been used in any other platform CCA. This work was divided into three stages. The first stage was the proposal of new concepts in distributed components. The second stage was the implementation of a CCA platform and exogenous and endogenous connectors. Finally, the third stage was modeling, implementing and testing High Performance Computing (I-1PC) applications using the proposed platform, called Forró. The results of case studies were satisfactory regarding the runtime. Based on this study it can be said that the proposed platform can present itself as a possible solution for applications composition from legacy code or methods.